Perception and customer loyalty in hotels within Ibadan metropolis, Ibadan, Oyo State (2018)
This research was carried out to assess the effect of perception on customer’s loyalty in hotels within Ibadan Metropolis., Random sampling was used to sample 150 respondents from the hotels in Ibadan. Data were analyzed using descriptive and inferential statistics. Overall perception towards tangibility was ranked at the strongly agree level (4.24), overall perception towards reliability was ranked at the strongly agree, level (412), overall perception towards responsiveness dimension was at the strongly agree level (4.26), overall perception towards assurance dimension was ranked at the agree level (4.19), overall perception towards empathy dimension was ranked at the strongly agree level (4.29). There is also a significant relationship between customer perception, overall loyalty (r= 0.458, p< 0.01), word of mouth fr= 0.858, p< 0.01), repeat patronage (r-0.813, p< 0.01), price insensitivity (r-0.460, p< 0.01). The study has found that there is significant relationship between perception of service (tangibles, responsiveness, assurance, ana empathy), word of mouth, repeat patronage and price insensitivity.